PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Nurhidayati, Nurhidayati; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is background overshadow by lowering of result of learning mathematics of student of class of III SD negeri 002 Jumrah Kecamatan Rimba Melintang, with the class mean 56,25. While complete criterion value minimize the ( KKM) Mathematics is 70. Among/Between student amounting to 24 people only 6 student people which which is not complete 18 (75%). Is for that performed a by Research of Class Action ( PTK) which aim to to increase result of learning mathematics of student of class IIII in SD Negeri 002 Jumrah Kecamatan Rimba Melintang of Teaching Year 2014 / 2015 through/ passing Applying Model the Instruction kontekstual. As for its problem formula is Whether/What Applying Model the Study Kontekstual can improve the result learn the Mathematics of Student of Class of III SD Negeri 002 Jumrah Kecamatan Rimba Melintang ?. this Subjek Research is student of class of IV SD Negeri 002 Jumrah amounting to 24 people. Instrument of data collecting of at this research is sheet aktifitas learn and student and also result of learning. From data analysis of is make-up of percentage aktifitas learn the first cycle I meeting 56,25%, second meeting mount to become 68,75% experiencing of improvement of first kesiklus II meeting become 81,25% and mount again at second meeting of cycle II become 93,75%. While percentage of aktifitas student of at first cycle I meeting 50% mounting at second meeting become 62,50% experiencing of improvement to first cycle II meeting become 75% and mount again at second meeting of cycle II become 87,50%. Research result in class of III SD Country 002 Jumrah prove that Applying Model the Instruction kontekstual can improve the result learn the mathematics of student of class of III SD Negeri 002 Jumrah Kecamatan Rimba Melintang.Keywords : Model The Study Kontekstual, Result of learning mathematics, PTK.